2021
DOI: 10.1111/nicc.12737
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between practice environment, job satisfaction and intention to leave in critical care nurses

Abstract: Background: Recent studies in the Kingdom of Saudi Arabia (KSA) have shown that the increasing nursing turnover in the health care industry has become a great source of concern. The overdependence on the supply of expatriate nurses (74%) and coronavirus disease 2019 (COVID-19) travel restrictions have exacerbated this staffing issue. Aims: To examine the relationship between perception of nursing practice environment (NPE), job satisfaction and intention to leave (ITL) among critical care nurses working in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…Previous national and international studies also highlighted this relationship between the work environment and intention to leave. Consistently with the results obtained, adequate work environments, thus being favorable to practice, should minimize intention to leave [1,8,12,24,43] and, consequently, the time/cost associated with integration processes and the risk of loss in quality of care provided during the replacement periods. Thus, ensuring favorable work environments is crucial to mitigate intentions to leave and promote nurse retention.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous national and international studies also highlighted this relationship between the work environment and intention to leave. Consistently with the results obtained, adequate work environments, thus being favorable to practice, should minimize intention to leave [1,8,12,24,43] and, consequently, the time/cost associated with integration processes and the risk of loss in quality of care provided during the replacement periods. Thus, ensuring favorable work environments is crucial to mitigate intentions to leave and promote nurse retention.…”
Section: Discussionmentioning
confidence: 60%
“…According to previous studies, factors that include work environment, emotional exhaustion, practice safety, and shortage of staff, associated with professionals' characteristics (such as age and education), can bring about nurses' desire to leave their unit, department, or organization. Inadequate staffing, including an increased workload in work environments unfavorable to nursing practices, usually motivates professionals to leave [4,7,12,13]. Professional development opportunities are also a determining factor.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that were associated with turnover intention among HCWs include poor job resources [ 45 ], low staff morale [ 45 ] and perceived high pandemic impact on practice [ 57 ]. Conversely, a study from Saudi Arabia found that a positive nursing practice environment was negatively correlated with turnover intention [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that the practice environment can affect nurses' mental and physical health (Silva & Marcolan, 2020), job satisfaction (Ogata et al, 2018; Suliman & Aljezawi, 2018), burnout (Hunsaker et al, 2015; Ogata et al, 2018), quality of life and well‐being (Misiak et al, 2020) and work engagement (Al‐Hamdan & Bani Issa, 2021). These effects are then followed by organizational ones such as nurse turnover (Alenazy et al, 2021) and nursing care quality (Aiken et al, 2011).…”
Section: Introductionmentioning
confidence: 99%